Pengaruh Kualitas Layanan Dan Harga Terhadap Keputusan Pengunaan Jasa Pada Dhea Laundry Manokwari - Henny Paulince Manobi; Makarius Bajari; Nurwidianto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the variables of service quality and price on the decision to use services at Dhea Laundry Manokwari The type of research used is a quantitative approach with the type of associative problem. The population in the study is Dhea Laundry consumers and the number of samples in this study is 75 respondents using the purposive sampling method as a sampling method. The data collection method uses primary data, namely observations, interviews, questionnaires and secondary data, namely books, journals, articles and topics related to research obtained from internet sites. This research instrument uses a Likert scale with a data analysis method, namely multiple linear regression analysis.The results of this study show that the independent variables, namely service quality and price, have a significant partial effect on the decision to use services and the results of simultaneous testing, namely service quality and price simultaneously affect the decision to use services.